A Choquet integral based interval Type-2 trapezoidal fuzzy multiple attribute group decision making for Sustainable Supplier Selection. (March 2022) - Xing, Yumei; Cao, Mingshuo; Liu, Yujia; Zhou, Mi; Wu, Jian
Highlights: A new partial order of interval type-2 trapezoidal fuzzy is defined. The Choquet integral with interval type-2 trapezoidal fuzzy is explored. The consensus reaching process is proposed for Sustainable Supplier Selection. Abstract: A new Choquet Integral based interval type-2 ( IT 2 TrFS ) trapezoidal fuzzy multiple attribute group decision making (GDM) for Sustainable Supplier Selection (SSS) is put forward in this article. It mainly consists of two aspects: (1) resolving the interaction between criteria (attributes); and (2) obtaining a consensual evaluation matrix acceptable to the group. The new partial order of IT 2 TrFS is proposed to better retain the original evaluation information of individual experts. Then, the Choquet integral with IT 2 TrFS is put forward to compute the criteria weight, so as to reflect interaction relationship between criteria. The distance of IT 2 TrFS is explored to calculate the consensus level, which is used to detect the inconsistencies among experts, and then a new feedback mechanism with considering benefit or cost criteria is developed to obtain the individual consensus evaluation matrix. Then, Shapley value based on fuzzy measure is used to determine weight of experts to reflect their global relationship. The final group evaluation matrix is obtained by integrating all individual consensus evaluation matrices. At last, a numerical case is presented to illustrate the effectiveness of the designed method.